THE RELATIONSHIP BETWEEN TYPES OF ADMISSION SELECTION AND ACADEMIC ACHIEVEMENT IN THE FIRST-YEAR STUDENTS DURING THE TRANSITION TO DISTANCE LEARNING DUE TO COVID-19 PANDEMIC - Nikla Sekar Salsabila; Kurnia Wahyudi; Yuni Susanti Pratiwi; Eko Fuji Ariyanto; Achadiyani Achadiyani (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: In 2019, there were three admission pathways in the Faculty of Medicine Universitas Padjadjaran (FMUP), which were SNMPTN (Seleksi Nasional Masuk Perguruan Tinggi Negeri), SBMPTN (Seleksi Bersama Masuk Perguruan Tinggi Negeri), and Seleksi Mandiri Universitas Padjadjaran (SMUP). SNMPTN was based on previous academic achievements in senior high school. SBMPTN was held through a highly competitive national examination, while SMUP was conducted through the test held by Universitas Padjadjaran. In their first year, batch 2019 students had to adapt to college life, and also to the transition into distance learning due to the COVID-19 pandemic. This study aimed to know whether types of student admission selection contribute to academic achievements of the first-year students in the Hemato-immunology system (HIS), where the learning process was held during the transition into distance learning.Methods: This study compared the academic achievement of first-year students (batch 2019) on the second semester’s second half, using their HIS Multidisciplinary Examination (MDE) scores, for three selection methods. The data were 256 MDE scores of those students. Statistical analysis was performed using One Way ANOVA test, followed by Post-hoc Tukey test.Results: There was a statistically significant difference of HIS MDE scores for each selection method. The highest mean was by SNMPTN group (68.29+10.44), followed by SBMPTN group (64.90+11.29) and SMUP group (63.25+9.95).Conclusion: Students of SNMPTN group, who were selected based on previous academic achievements in senior high school, had higher HIS MDE scores than the other groups.